2012
DOI: 10.17477/jcea.2012.11.2.027
|View full text |Cite
|
Sign up to set email alerts
|

The Logic of Japan's Free Trade Agreements (FTA) with ASEAN

Abstract: Among political scientists, Japan's free trade agreements (FTA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…As a result, Tokyo has primarily sought a bilateral form in order to assert the particular interest in the context of PTAs. In exchange, the nation usually provides partner countries with developmental assistance and other programs to accommodate their needs (Dent, 2005; Yamamoto, 2012, 2013).…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, Tokyo has primarily sought a bilateral form in order to assert the particular interest in the context of PTAs. In exchange, the nation usually provides partner countries with developmental assistance and other programs to accommodate their needs (Dent, 2005; Yamamoto, 2012, 2013).…”
Section: Theorymentioning
confidence: 99%
“…For instance, the Japanese External Trade Organization has found that <50% of eligible users have utilized Japan's bilateral PTAs over the last decade. It is due to the offset benefits of PTAs through the voluntary application process for using the agreements, floating exchange rates, complicated rules of origin and other mechanisms that allow firms to trade ‘freely’ without the agreements (Ravenhill, 2010; Yamamoto, 2012). Hence, this article expects joint WTO membership between states to stimulate bilateral PTAs.…”
Section: Theorymentioning
confidence: 99%